2019
DOI: 10.1016/j.patcog.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Sparse autoencoder for unsupervised nucleus detection and representation in histopathology images

Abstract: Histopathology images are crucial to the study of complex diseases such as cancer. The histologic characteristics of nuclei play a key role in disease diagnosis, prognosis and analysis. In this work, we propose a sparse Convolutional Autoencoder (CAE) for fully unsupervised, simultaneous nucleus detection and feature extraction in histopathology tissue images. Our CAE detects and encodes nuclei in image patches in tissue images into sparse feature maps that encode both the location and appearance of nuclei. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(88 citation statements)
references
References 53 publications
0
88
0
Order By: Relevance
“…The necrosis CNN was retrained only once in this study, because it achieved sufficient prediction accuracy. The training and re-training steps of both CNNs involve cross-validation to assess prediction performance and avoid overfitting (Hou et al, 2017). See the Method Details for an in-depth description of this process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The necrosis CNN was retrained only once in this study, because it achieved sufficient prediction accuracy. The training and re-training steps of both CNNs involve cross-validation to assess prediction performance and avoid overfitting (Hou et al, 2017). See the Method Details for an in-depth description of this process.…”
Section: Resultsmentioning
confidence: 99%
“…The CNN and the CAE are designed to have relatively high resolution input such that one can recognize individual lymphocytes. We have chosen to apply unsupervised CAE pre-training because many studies have shown that it boosts the performance of the CNN, please refer to our technical report (Hou et al, 2017). Using the lung adenocarcinoma (LUAD) patches, we empirically showed that the CNN without pre-training achieved significantly lower area under the curve (AUC).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Visually examination of H&E stained histopathology slides by pathologists is a standard clinical practice to diagnose and grade different type of cancers. Many previous studies have been focusing on detection/segmentation of tissue objects [33] [34], or extracting histological image features to assist pathologists in computer-aided tumor diagnosis [5] [11]. Until recently, there are two existing studies [15][17] which explored and found that some gene mutations (e.g., SPOP, KRAS mutations) are predictable by using histological image features in prostate and lung cancer pathology slides.…”
Section: Discussionmentioning
confidence: 99%